Determinants of traditional agricultural exports in Nigeria: an application of cointegration and correction model (2003)
The study aimed to derive estimates of factors influencing Nigeria’s agricultural exports to five principal countries - United States, The Netherlands, United Kingdom, Germany, and France, with the aid of error correction representation procedures. The analysis was carried out with the data collected on Nigeria primary exports - cocoa, palm kernel, and rubber, over 38 years (1960 - 1997). Agricultural commodity exports to the selected countries were influenced by the domestic output, population growth, quantity supplied by competing countries, index of industrial production of importing countries, and time trend. However, the domestic output and population growth rate were the most significant factors influencing agricultural exports in the importing countries. In addition, there is high feedback captured by the coefficients of the error correction mechanism. There seems to be an instantaneous change in the short-run equilibrium to long-run equilibrium values of agricultural exports as a result of policy changes in the regressors. Efforts to boost agricultural exports from Nigeria will need to incorporate policy measures to improve producer prices, enhance the quality of the products, and ensure timely exports of the commodities, especially those with a positive relationship between the index of industrial production of importing countries and Nigeria’s exports. With short-run policy changes by the importing countries, the rate of response by Nigerian producers through exports will be almost spontaneous, as indicated by the coefficient of the error correction mechanism ECM (-1).